The Effect of Brain Drain on the Economic Growth of Developing Countries: Evidence from Pakistan - Khan, Assad Mehmood (Annals of Human and Social Sciences, 2024)
The escalating trend of brain drain in developing countries like Pakistan necessitates urgent attention from political leadership to avert potential impediments to national development. Objective of study is to explore the root causes, consequences, and ramifications of brain drain on Pakistan's economic trajectory. This research employs a mixed-methods approach, integrating qualitative and quantitative practices. While, data analysis is carried by employing the ordinary least squares (OLS) technique to evaluate relevant data and trends. The results reveal a negative correlation between brain drain and economic progress, highlighting the challenges posed by talent migration to sustainable development. Notably, the study also revealed an inverse correlation between brain drain, remittances, and economic advancement, while highlighting a positive linkage between human capital augmentation and economic prosperity within the Pakistani context. Drawing from these insights, the study recommends for targeted policy interventions, mitigating adverse effects of brain drain on Pakistan's economic landscape.